Using herbal and traditional medicinal products is the risk factor of adrenal insufficiency in Thailand: The retrospective cohort study - W. Manosroi (2020)
© Journal of the Medical Association of Thailand. Background: Herbal and traditional medicinal products (HTM) are widely used worldwide, particularly in the Asian region. Adulteration of undeclared glucocorticoids in these products may lead to adrenal insufficiency (AI). Objective: To investigate the relationship between HTM usage and the risk of AI. Materials and Methods: A 7-year retrospective study of 369 adult patients who had undergone the ACTH stimulation test was conducted in a tertiary care medical center in Thailand. An adjusted risk ratio was used to compare the incidence of AI between patients using HTM and those not using HTM. Results: Overall, 44.7% of the patients who reported using HTM were diagnosed with AI with adjusted risk ratio of 1.71 (95% CI 1.01 to 2.94). Cushingoid appearance was found to be significantly related to AI. Conclusion: There is a significantly higher incidence of AI in patients who use HTM. Healthcare professionals should be concerned about AI in the patients who have a history of HTM use.